2021
DOI: 10.3892/etm.2021.11084
|View full text |Cite
|
Sign up to set email alerts
|

P2X7R antagonist protects against renal injury in mice with adriamycin nephropathy

Abstract: Activation of the purinergic P2X7 receptor (P2X7R) has been associated with the development of experimental nephritis. Therefore, the current study aimed to explore the mechanism of P2X7R in renal injured mice with adriamycin (ADR) nephropathy. The protective effect of a P2X7R antagonist on the kidneys of mice with ADR nephropathy was also evaluated. Nephropathy was induced by a single intravenous injection of ADR (10.5 mg/kg). A total of 6 h before the model was established, the P2X7R antagonist A438079 (100,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A robust increase of plasma IL-1β was observed in LPS challenge mice model, and oral treatment with compound 32 resulted in suppression of plasma IL-1β in a dose related manner (Figure a). To evaluate the therapeutic potential of compound 32 on glomerulonephritis, compound 32 was administered orally for 2 weeks in mice with adriamycin-induced glomerulonephritis. , We found that treatment of the mice model with compound 32 improved the urine albumin-to-creatinine ratio (UACR) in a dose related manner (Figure b). These data confirmed that NLRP3 inhibition was effective against glomerulonephritis.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…A robust increase of plasma IL-1β was observed in LPS challenge mice model, and oral treatment with compound 32 resulted in suppression of plasma IL-1β in a dose related manner (Figure a). To evaluate the therapeutic potential of compound 32 on glomerulonephritis, compound 32 was administered orally for 2 weeks in mice with adriamycin-induced glomerulonephritis. , We found that treatment of the mice model with compound 32 improved the urine albumin-to-creatinine ratio (UACR) in a dose related manner (Figure b). These data confirmed that NLRP3 inhibition was effective against glomerulonephritis.…”
mentioning
confidence: 97%
“…Compounds 21 and 22, which were modified with methyl groups for the purpose of reduction of lipophilicity showed slight decreases in IL-1β inhibitory activities. Introduction of an i-Pr substituent at the ortho-position did not lead to an improvement of IL-1β inhibitory activity (23). Therefore, we next investigated the effect of substituents in the meta-position with respect to compound 20, which exhibited moderate potency along with low lipophilicity.…”
mentioning
confidence: 99%